Dermatological manifestations in COVID-Related illness in children: A retrospective observational study at a tertiary care hospital of Eastern India - Radheshyam Purkait; Kakali Roy; Nivedita Manna; Moumita Samanta; Tapan Kumar Sinha Mahapatra (Wolters Kluwer Medknow Publications, 2023)
Objectives: To identify the spectrum of cutaneous manifestations and to evaluate temporal relationship between each type of dermatological lesions and the severity of COVID-19-related illness in the pediatric population. Subjects and Methods: Retrospective observational study on 35 children (upto12 years) from Kolkata and different district areas of West Bengal, admitted to our tertiary care hospital with COVID-related illnesses (COVID-19 and/or multisystem inflammatory syndrome in children [MIS-C]). Results: Maculopapular rash was heading the list (n = 18, 51.4%) followed by chilblain-like lesions (n = 12, 34.2%), vasculistic lesion (n = 8, 22.8%), vesicular rash (n = 5, 14.3%), and urticaria (n = 3, 8.5%). In majority of patients (n = 26, 74.2%), dermatologic manifestations proceeded (n = 16, 45.7%) or merged (n = 10, 28.6%) with the onset of systemic symptoms. In rest of the patients (n = 9, 25.7%), skin manifestations occurred after the systemic symptoms, particularly in vascular lesions. 57.1% children required pediatric intensive care unit (PICU) admission. All children with vasculitis (n = 8) required PICU admission and 87.5% (n = 7) of them needed inotrope support. Intravenous immunoglobulin (IVIG) was mostly given in children with chilblains (n = 11, 92%). Methylprednisolone and repeat dose of IVIG was mostly needed in patients with vasculitis (75% and 25% of vasculitis children, respectively). The duration of PICU stay was least in patients with vesicular rash (4.4 ± 2.5 days) and longest in vasculistic lesions (18.75 ± 1 days), highest being 56 days. The overall mortality rate among MIS-C patients with cutaneous manifestations was 25.7% (n = 9) while patients with vasculistic lesions had the highest mortality rate of 50% (n = 4). Conclusion: Our study finding reveals that COVID-related disease severity is highly depends on the type of skin lesions but not just on mere occurrence of skin manifestations. Lesions such as maculopapular, chilblains, and vesicular rash had good prognosis and urticaria and vasculitis had poor prognosis.